2000
DOI: 10.1038/35042558
|View full text |Cite
|
Sign up to set email alerts
|

Microseismological evidence for a changing wave climate in the northeast Atlantic Ocean

Abstract: One possible consequence of a change in climate over the past several decades is an increase in wave heights, potentially threatening coastal areas as well as the marine industry. But the difficulties in observing wave heights exacerbates a general problem of climate-change detection: inhomogeneities in long-term observational records owing to changes in the instruments or techniques used, which may cause artificial trends. Ground movements with periods of 4-16 seconds, known as microseisms, are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 20 publications
5
82
0
Order By: Relevance
“…Grevemeyer et al 2000). Most of these studies, based on observations, indicated a general upward trend in wave heights (e.g.…”
Section: Wave Climatementioning
confidence: 99%
“…Grevemeyer et al 2000). Most of these studies, based on observations, indicated a general upward trend in wave heights (e.g.…”
Section: Wave Climatementioning
confidence: 99%
“…Several papers have dealt with the evolution of the wave climate in the North Atlantic and the North Sea (Kushnir et al 1997, Günther et al 1998, WASA Group 1998, Grevemeyer et al 2000. They document an increase in mean wave heights and extreme values in the last few decades for this area by examining observations or results from wave models or indirect measurements, such as the microseismic activity in the coastal area.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Especially volatile inter-annual behavior is notable at North Atlantic stations (Figures 2, S2, and S3) [Grevemeyer et al, 2000;Essen et al, 2003]. Station-specific, regional, and global linear trends evaluated via L 2 -norm regression with bootstrap parameter estimates display a bias for positive regression slopes (Figures 2 and S4).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that climate change may affect the frequency, distribution, and/or intensity of storms and associated ocean wave activity, for example in hurricanes affecting the eastern U.S. and Caribbean [Emanuel, 2005;Federov et al, 2010], in northern Pacific winter cyclones [e.g., Graham and Diaz, 2001;Bromirski et al, 2005a;Lambert and Fyfe, 2006], and in extratropical storms affecting northern Europe [e.g., Grevemeyer et al, 2000;Essen et al, 2003]. In this paper, we concentrate on global winter period storms and demonstrate that microseism data from existing Global Seismographic Network (GSN) [Butler et al, 2004] infrastructure provides a valuable real-time metric for comparing extreme coastal wave events across decadal time spans.…”
Section: Introductionmentioning
confidence: 99%